Refrozen of bovine sperm as an alternative to improve the sperm quality of semen - Mancheno Herrera, Carlos Andrés; Andino Nájera, Pablo Rigoberto (SATHIRI, 2022)
The objective was to evaluate the effect of re-freezing bovine sperm on the sperm quality of thawed semen. For this, the semen was thawed in water at 56 oC for 12 seconds to simulate a maximum seminal aggression, the contents of the straws were poured into test tubes to keep them tempered at 37 oC and incubated with 5 ml of Tyrode medium for 15 minutes. After this time, the microscopic analysis of the semen was carried out, two centrifugations were carried out 300 rpm / 5 minutes - 800 rpm / 10 minutes and the sperm concentration was determined with the help of a digital cell counter to dilute the semen; The stabilization and conditioning of the sperm was carried out at room temperature (14-20 oC) for 45 minutes and under ultraviolet light, then the straws were packed and sealed using 0.5 ml straws and polyvinyl alcohol to seal them. The temperature curves and finally the refreezing in nitrogen vapors were carried out. For hypothesis testing, the analysis techniques of ADEVA (Analysis of Variance) and separation of measurements by the Waller Duncan multiple range method were used at a significance level of p
Keywords: refrozen; sperm; bovine; seminal quality; semen